2017
DOI: 10.3389/fped.2017.00222
|View full text |Cite
|
Sign up to set email alerts
|

Thirty Years of Sweat Chloride Testing at One Referral Center

Abstract: ObjectiveTo conduct a descriptive analysis of the sweat test (ST), associating ST results with epidemiological data, CFTR (cystic fibrosis transmembrane conductance regulator) mutations and reasons to indicate the ST, as well as correlating sweat sodium and sweat chloride concentrations in subjects.MethodsRetrospective survey and descriptive analysis of 5,721 ST at a university referral center.ResultsThe inclusion of the subjects was based on clinical data related with cystic fibrosis (CF) phenotype. The sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
2
6
0
Order By: Relevance
“…In the literature, we did not have a consensus regarding the maximum value to sweat weight where we can consider the sweat test as acceptable to CF diagnosis. Also, as previously reported by us and discussed in our present data, we found a negative correlation between sweat weight and concentration of chloride [ 26 ]. In this scenario, we believe that this fact is not important when the final sweat weight is bigger than 75 mg until values around 100 mg, but when we have a highest sweat weight, a major influence in concentration of chloride can be achieved and representing an alteration in the classification of the patient, mainly, in cases, with normal or borderline values in sweat test.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the literature, we did not have a consensus regarding the maximum value to sweat weight where we can consider the sweat test as acceptable to CF diagnosis. Also, as previously reported by us and discussed in our present data, we found a negative correlation between sweat weight and concentration of chloride [ 26 ]. In this scenario, we believe that this fact is not important when the final sweat weight is bigger than 75 mg until values around 100 mg, but when we have a highest sweat weight, a major influence in concentration of chloride can be achieved and representing an alteration in the classification of the patient, mainly, in cases, with normal or borderline values in sweat test.…”
Section: Discussionsupporting
confidence: 93%
“…In our data, a large number of the evaluated individuals had a change in the outcome of the CF diagnosis, considering the increase in sweat weight collected in the sweat test. At the same time, we showed that there is a negative correlation between the chloride ion and the sweat weight, and this fact was observed in the literature [ 26 ], but other studies should be performed to close the idea behind this issue. Thus, the sweat test should be redone even when a sweat value was obtained according to the guidelines (≥ 75 mg) and there was still clinical suspicion and/or positive neonatal screening.…”
Section: Discussionsupporting
confidence: 70%
“…All patients were attended at the Referral Center of a University Hospital and had equal access to: (i) genetic counseling, (ii) tools for diagnosis and functional analysis of CFTR, (iii) outpatient and therapeutic management, (iv) availability of drugs and (v) psychological support. Sweat tests were performed in outpatient settings 15 . Induction of sweating and sweat collection were performed according to the Gibson-Cooke method (1959) 16 , and chloride concentration was quantified by titrations with mercury nitrate 1720 .…”
Section: Cases Under Study and Methodsmentioning
confidence: 99%
“…The patient suffered from bronchiectasis, but no significant change was found in the chest CT between 2014 and 2016. Although we did not obtain results of the sweat test, a previous study identified that several damaging CFTR mutations, including homozygous F508del/F508del mutations, were associated with high sweat chloride levels exceeding 60 mEq/L (36). Therefore, the sweat test is an important tool for CF diagnosis, particularly in the absence of the identification of mutations in the CFTR gene.…”
Section: Discussionmentioning
confidence: 84%